Genetic Effects Influencing Egger Traits From Diallel Mating System - Rashbehari Singh K (Department of Poultry Science, College of Veterinary Science, 1983)
A 3 x 3 diallel cross was made using IWP, IWN and F strains of White Leghorn at the All India Co-ordinated Research Project on Poultry for Eggs, Thrissur centre. Age at first egg in days, body weight at 20 and 40 weeks of age in grammes, egg number up to 280 days of age and egg weight (g) at 38 weeks of age were recorded for all the nine genetic groups.